Асимптотичний підхід до вирішення дискретних екстремальних задач з інтервальними даними - Perepelitsa, V. A.; Tereshchenko, Ye. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A polynomial two-level algorithm for the linear contraction of criteria for the problem of covering an interval-weighted graph with stars is offered when the objective function tends to a maximum. The sufficient conditions for the asymptotic accuracy of the algorithm is substantiated.